Cognitive achievements in school-age children born following assisted reproductive technology treatments: A prospective study. (April 2021) - Farhi, Adel; Gabis, Lidia V.; Frank, Shay; Glasser, Saralee; Hirsh-Yechezkel, Galit; Brinton, Louise; Scoccia, Bert; Ron-El, Raphael; Orvieto, Raoul; Lerner-Geva, Liat
Abstract: Background: While assisted reproductive technology is increasingly prevalent, there is concern amid conflicting findings reported regarding the long-term outcomes of children born following these treatments. The aim of this research was to investigate aspects of cognitive development in early school-age Israeli children born following assisted reproductive technology (ART) treatments, compared to those spontaneously conceived (SC). Method: This prospective follow-up study was based on an Israeli cohort recruited from June 2006 to December 2008, that included 561 women whose pregnancies were achieved by ART treatments and 600 women whose pregnancies were SC. When the children were 7–8 years old, 759 of their mothers were interviewed by telephone, and 294 were came for developmental assessment. The examination included: Kaufman Brief Intelligence Test; Kaufman Assessment Battery for Children (arithmetic only); Test of Everyday Attention for Children; Beery-Buktenica Developmental Test of Visual-Motor Integration and Supplemental Test for Visual Perception; Rey-Osterrieth Complex Figure Test; Aleph-ad-Tav Hebrew reading and writing; Tavor Picture Naming Expressive Vocabulary Test. Multivariable analyses were adjusted for maternal years of education (≤12, 13+) at child's birth and child's sex. Results: Cognitive function, visual-motor ability, attention, and verbal skills of children born after ART treatments were similar to those of SC children, upon both univariate and multivariable analysis. Conclusion and implications: No significant differences were found between the ART and SC groups on any of the measures examined. This finding offers couples seeking ART treatments improved information regarding child development during the important and formative school years. What this paper adds: Increasing rates of ART treatments arouse concern about long-term outcomes for offspring, and conflicting findings have been reported with respect to the skills necessary to their academic success. This prospective follow-up study compared school-age children born following ART with spontaneously-conceived children. Children were examined by developmental psychologists, and cognitive function, visual-motor, attention, verbal, and performance skills were similar in both groups. Highlights: Assisted reproductive treatments arouse concern for offspring's long-term outcomes. Conflicting findings have been reported regarding their academic success. School-age children born following ART and those spontaneously-conceived were compared. Developmental psychologists examined children in both groups. Cognitive, visual-motor, attention and verbal skills were similar in both groups.